Green culture an A-to-Z guide - Wehr, Kevin 1972-. (Los Angeles, [Calif.] London SAGE, 2011)
From green Hollywood to green spirituality, green art and green restaurants, this volume contains 150 articles exploring the on-going paradigm shift in culture and lifestyles toward promoting a sustainable environment.
Includes bibliographical references and index.
Keywords: Sustainability; Sustainable living; Environmentalism; Electronic books